Grey system based on flux estimation for vector control of asynchronous motors - Saman, Mehmet; Karaköse, Mehmet; Akin, Erhan (My University, 2011)
In vector control of asynchronous motors, using voltage model for flux estimation ensures many advantages as regarding. Accuracy of estimation of stator fluxes is important in this model. Some inaccuracies occur due to uncertainty of parameters and measurement errors in the flux estimation. Grey systems theory provides simplistic methods for systems containing uncertainty. In this paper, the flux estimation is taken into account as a grey system and appropriate solution is introduced. © 2011 IEEE.
Asenkron motorlarin vektör kontrolünde gri? si?stem tabanli aki tahmi?ni?
2011 IEEE 19th Signal Processing and Communications Applications Conference, SIU 2011 -- 20 April 2011 through 22 April 2011 -- Antalya -- 85528
Keywords: Intelligent systems; Measurement errors; Motors; Signal processing; System theory; Uncertainty analysis; Flux estimation; Grey systems; Stator flux; Vector controls; Voltage model; Estimation